2008
DOI: 10.1159/000111639
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Services for Hereditary Breast/Ovarian and Colorectal Cancers – Physicians’ Awareness, Use and Satisfaction

Abstract: Objectives: In 2000, the Ministry of Health in Ontario, Canada, introduced a publicly funded program to provide genetic services for hereditary breast/ovarian and colorectal cancers. We surveyed physicians to determine their awareness, use and satisfaction with this program. Methods: A self-administered questionnaire was mailed to a random sample of 25% of Ontario family physicians and all gynecologists, oncologists (radiation, surgical and medical), gastroenterologists and general surgeons. Results: Response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 47 publications
2
46
4
Order By: Relevance
“…The most commonly cited barrier category within this theme was a general lack of genetic knowledge (n = 24 cited in 20/38 studies); this included specific barriers around PCPs' self-reported lack of confidence in their own knowledge about genetics in general (n = 7) 6-12 and about clinical genetics, 13 an interest in gaining insight regarding the genetic background of a disease, 14 and a lack of confidence in their ability to perform core competencies such as taking an FH, 15 including a lack of knowledge about what FH information to collect. 16 Among the several skill-related barriers identified, the most commonly cited (n = 16 citations in 16/38 studies) was a lack of confidence their ability to counsel patients about genetic risk and to manage them.…”
Section: Knowledge and Skillsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most commonly cited barrier category within this theme was a general lack of genetic knowledge (n = 24 cited in 20/38 studies); this included specific barriers around PCPs' self-reported lack of confidence in their own knowledge about genetics in general (n = 7) 6-12 and about clinical genetics, 13 an interest in gaining insight regarding the genetic background of a disease, 14 and a lack of confidence in their ability to perform core competencies such as taking an FH, 15 including a lack of knowledge about what FH information to collect. 16 Among the several skill-related barriers identified, the most commonly cited (n = 16 citations in 16/38 studies) was a lack of confidence their ability to counsel patients about genetic risk and to manage them.…”
Section: Knowledge and Skillsmentioning
confidence: 99%
“…SyStematic Review for cancer susceptibility, 15,17 as well as citing a lack of overall confidence in assessing patient risk. 7,23 In their assessment of 860 US PCPs, Vig et al 24 found that 38.3% were uncomfortable with making screening and prevention recommendations and were uncertain about which patients are medically appropriate to refer.…”
Section: Genetics In Medicine | Volume 17 | Number 3 | March 2015mentioning
confidence: 99%
See 3 more Smart Citations